Strategi pengembangan agrowisata jeruk petik sendiri di Kecamatan Merek Kabupaten Karo - Simatupang, Jones P; Pakpahan, Helena Tatcher; Panataria, Lince R.; Simatupang, Donny; Hutapea, Kenal (Jurnal Agrotek Ummat, 2022)
Agrotourism is a series of tourism activities that develop agricultural activities as the main target of tourism. Agritourism covers various aspects of agriculture, including natural landscapes, agricultural activities, diversity in agricultural production, agricultural technology, and agricultural customs prevailing. The research purpose was to analyze and identify internal and external factors and develop appropriate strategies for orange self-picking agrotourism. The research was carried out in orange self-picked agrotourism in Merek District, Karo Regency, North Sumatra Province purposively. The research sample was 40 samples. Data analysis was carried out using the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation) matrix, SWOT matrix, and AHP (Analytical Hierarchy Processes). The research results determined the 12 internal factors and 12 external factors. In addition, there were 13 strategies for developing the orange self-picking agrotourism.